2015
DOI: 10.3402/gha.v8.26065
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of mother-to-child HIV-1 transmission in Burkina Faso: evaluation of vertical transmission by PCR, molecular characterization of subtypes and determination of antiretroviral drugs resistance

Abstract: BackgroundVertical human immunodeficiency virus (HIV) transmission is a public health problem in Burkina Faso. The main objective of this study on the prevention of mother-to-child HIV-1 transmission was to determine the residual risk of HIV transmission in infants born to mothers receiving highly active antiretroviral therapy (HAART). Moreover, we detect HIV antiretroviral (ARV) drug resistance among mother–infant pairs and identify subtypes and circulating recombinant forms (CRF) in Burkina Faso.DesignIn thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…The study revealed genetic mutations that induce resistance such as M184V, Y115F, K103N, Y181C, V179E and G190A. The main strains of infection in this study group were CRF06_CPX and CRF02_AG [20].…”
Section: Prevalence and Different Types Of Drug Resistance Mutationsmentioning
confidence: 89%
See 1 more Smart Citation
“…The study revealed genetic mutations that induce resistance such as M184V, Y115F, K103N, Y181C, V179E and G190A. The main strains of infection in this study group were CRF06_CPX and CRF02_AG [20].…”
Section: Prevalence and Different Types Of Drug Resistance Mutationsmentioning
confidence: 89%
“…Major resistance associated mutations in reverse transcriptase gene were observed in about one in three of the ART naïve and experienced children respectively while minor mutations were observed in protease gene in only five out of the total 140 children involved in the study [19]. Sagna et al [20] identified resistant strains to ARV drugs and determined the subtypes and circulating recombinant forms (CRF) of HIV-1 among mother-infant pairs in a study carried out in Burkina Faso. The study revealed genetic mutations that induce resistance such as M184V, Y115F, K103N, Y181C, V179E and G190A.…”
Section: Prevalence and Different Types Of Drug Resistance Mutationsmentioning
confidence: 97%
“…Data on number of pregnancies or previously infected/exposed children from the 69 women were not available in clinical reports provided by GQ clinicians, but it is unlikely that these women were exposed to ART before participating in the PMTCT program. As most of the included 69 women were under ART at sampling leading to low VL, we were able to obtain resistance data from 38 women, representing 55.1% of the whole cohort, a high rate compared to other reports performed on treated pregnant women [38,48,49]. Following WHO recommendations for resistance testing in limited resources settings, we used DBS for sample collection (only four drops of eluted dried blood) to obtain the HIV sequence, whereas all resistance studies in pregnant women apart from one in Tanzania [43], were carried out on higher volumes of plasma or whole blood [3842,44–51].…”
Section: Discussionmentioning
confidence: 99%
“…The Human Immunodeficiency Virus (HIV) is an etiological cause of Acquired Immunodeficiency Syndrome (AIDS) [1] [2] [3] [4] which is a major worldwide threat particularly in Africa as it continues to claim millions of lives and still remind incurable. Globally, over 35.4 million people are living with the HIV and about 63% -70% of the HIV infected individuals at the end of 2012 are living in Sub-Saharan Africa [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Sub-Saharan Africa represent 10% of the world's population but unfortunately 67% of HIV infected adults and 90% of HIV infected children live in Sub-Saharan Africa and about three quarters of all AIDS deaths occurred in this region [7] [8]. It is estimated that roughly there are 7000 new HIV infections every day and nearly 97% of these, come from developing countries and about 60% are from Sub-Saharan Africa [4].…”
Section: Introductionmentioning
confidence: 99%